THE CENSORSHIP LISTS OF 1944 – A MATRIX FOR POLITICAL ACTION - Margaret Poppetrova (Издател)
After the coup on September 9, 1944, and the establishment of the government of the Fatherland Front (September 1944) restrictive measures were taken in relation to literature with pro-fascist and fascist content, publications propagandizing National Socialism and the policy of the Third Reich, as well as those with anti-Soviet, anti-British and anti-American content. The first two lists of such publications appear at the end of 1944. However, they also include a wide range of publications that have nothing to do with the literature officially declared as subject to confiscation. Impressive is the large number of publications related to the Bulgarian monarchy, as well as the literature devoted to the national question, above all to the subject of Macedonia. It can be reasonably argued that these lists serve as a kind of matrix for political restrictions, various repressions and mark the beginning of institutional censorship in the country.